Thresholds of biological action of ultrasound - AKOPYAN, Valentin (Archives of Acoustics, 1984)
The character of the regulative mechanisms in a cell depends on the degree to which the intracellular medium has changed and, hence, on the degree of change in the cell membrane permeability which is dependent on the intensity of ultrasound action. Therefore, for biological action, the threshold intensity is the intensity below which there appear no changes in the cell membrane permeability. Judging by well-known data, this threshold is ≤ 0.1 kWm^{-2} (~1 MHz). In a certain interval of higher ultrasound intensitities no visible changes are observed in the structure and function of cells, which is due to the development of the regulative processes. The upper limit of this interval represents another "registered" threshold of biological action of ultrasound 1 kWm^{-2}). In a definite interval of ultrasound intensities exceeding 1 kWm^{-2} the observed biological effects are reversible. The upper limit of this interval (10 kWm^{-2}) can be taken as still another threshold.